2023
DOI: 10.1097/yic.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Age or age of onset: which is the best criterion to classify late-life depression?

Abstract: In late-life depression (LLD), several differences between patients whose first episode is reported after age 65 (late-onset depression, LOD) and those with early-onset depression (EOD) might reflect the effects of brain ageing. To test this hypothesis, we analysed the impact of current age and age at illness onset on a number of clinical and cognitive manifestations in 438 outpatients with major depressive disorder aged >60 years, treated with venlafaxine for 12 weeks. When compared to the EOD group, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…After submitting request forms to the NIMH, we were authorised to analyse 482 CO-MED patients and 438 IRL-GRey participants prior to this study, we have already used CO-MED data to investigate SI persistence during antidepressant treatment and clinical differences between severe and moderate SI [47,48]. Instead, IRL-GREY data have been analysed by our research group to test different diagnostic criteria for late-life depression [49].…”
Section: Samples and Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…After submitting request forms to the NIMH, we were authorised to analyse 482 CO-MED patients and 438 IRL-GRey participants prior to this study, we have already used CO-MED data to investigate SI persistence during antidepressant treatment and clinical differences between severe and moderate SI [47,48]. Instead, IRL-GREY data have been analysed by our research group to test different diagnostic criteria for late-life depression [49].…”
Section: Samples and Treatmentsmentioning
confidence: 99%
“…All participants were enrolled after obtaining their written informed consents. This research group certifies that data collected from participants in the CO-MED and IRL-GREY trials were exclusively used for scientific research: prior to access, the aims of our investigations were clearly stated in the request forms [47][48][49].…”
Section: Samples and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, lateonset depression (LOD) and early-onset depression (EOD) distinguished by the age of rst onset appear to have distinct characteristics (3)(4)(5). While a systematic review has indicated no clinical differences between EOD and LOD groups except for a family history of depression (6), other comparative studies have shown higher prevalence of cognitive decline, somatic complaints, and vascular risk factors in LOD than in EOD (3,7,8). LOD also demonstrates distinct functional network patterns, suggesting that it has different pathological changes from EOD, as evidenced by functional magnetic resonance imaging (MRI) studies (9).…”
Section: Introductionmentioning
confidence: 99%